2012
DOI: 10.1111/fwb.12079
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale effects of impoundments on genetic structure of creek chub (Semotilus atromaculatus) in the Kansas River basin

Abstract: Summary 1. Habitat fragmentation has been implicated as a primary cause for the ongoing erosion of global biodiversity, yet our understanding of the consequences in lotic systems is limited for many species and regions. Because of harsh environmental conditions that select for high colonisation rates, prairie stream fishes may be particularly vulnerable to the effects of fragmentation. Hence, there is urgent need for broader understanding of fragmentation in prairie streams such that meaningful conservation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 64 publications
6
23
2
Order By: Relevance
“…The letters state whether groups differed significantly from one another in one-sided t-tests assuming unequal variance of groups, after Holm's correction of P-values for multiple tests had been applied. These results are similar to those of Mitsui, Isagi & Setoguchi (2010), Kondo, Nakagoshi & Isagi (2009), Hudman & Gido (2013 and Van Looy et al (2009). This is different from what has been found for the riparian tree species black poplar (Smulders et al, 2008), a wind-pollinated and wind-dispersed species.…”
Section: Modelcontrasting
confidence: 50%
See 2 more Smart Citations
“…The letters state whether groups differed significantly from one another in one-sided t-tests assuming unequal variance of groups, after Holm's correction of P-values for multiple tests had been applied. These results are similar to those of Mitsui, Isagi & Setoguchi (2010), Kondo, Nakagoshi & Isagi (2009), Hudman & Gido (2013 and Van Looy et al (2009). This is different from what has been found for the riparian tree species black poplar (Smulders et al, 2008), a wind-pollinated and wind-dispersed species.…”
Section: Modelcontrasting
confidence: 50%
“…For aquatic species, several studies have found similar genetic isolation effects among populations separated by physical barriers (Horreo et al, 2011; 2012; Franssen, 2012;Hudman & Gido, 2013), but this issue has received less attention in riparian species. Moreover, Bayesian clustering revealed different populations on either side of physical barriers in all catchments.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For both F. validus and F. erichsonianus , gene flow from down‐ to upstream populations was lower in impounded streams compared to unimpounded streams, which is consistent with the expected response to stream habitat fragmentation (Fluker et al, ; Hudman & Gido, ; Meffe & Vrijenhoek, ). In contrast, crayfish populations in up‐ and downstream sections of unimpounded streams displayed high genetic connectivity and bidirectional dispersal and gene flow.…”
Section: Discussionsupporting
confidence: 78%
“…Collectively, the results from this study and a recent body of work on similar stream‐inhabiting fishes (i.e. Skalski et al ., ; Franssen, ; Hudman & Gido, ) suggest that reservoir‐induced fragmentation can affect gene flow and genetic structure in stream fishes over relatively brief timescales.…”
Section: Discussionmentioning
confidence: 99%